Men and women amongst themselves : gender-specific developments in dual male and female occupations and differences during training - Kroll, Stephan [Verfasser] (My University, 2021)
"A sharp decline in female participation in the dual vocational system pursuant to the Vocational Training Act (BBiG) or the Crafts and Trades Regulation Code (HwO) has been evident since the start of the 1990s. By 2019, the number of women as a proportion of all trainees had fallen by five percentage points. In the area of responsibility of trade and industry, it was even the case that a decline of just under eight percentage points was recorded. What impact is this having on developments in occupational structure? This article uses the Vocational Education and Training Statistics to illustrate how the ratio of occupations dominated by men or by women has shifted over the past three decades. It also investigates which differences in training success may emerge as a result of such an unequal distribution of the genders." (author's abstract; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 2.4.5 Gender Mainstreaming; P 1.3 Frauen; P 1.4 Männer; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); 370; Duales System; Geschlechterverteilung; Frauenberuf; Männerberuf; Berufsstruktur; Ausbildungsverlauf; Berufsbildungsstatistik